Sports in Gaining Life Skills: A Study on 10-14 Years Old Students - Karademir, Tamer (Asian Journal of Education and Training, 2020)
The study aims to investigate how the participation of secondary school students in sportive activities affects their life skills. For this purpose, the study included 708 voluntary students, 396 males, and 312 females, in the 2019-2020 education period. In the study, the Life Skills Scale for Sport (LSSS) was used as the data collection tool to evaluate the levels of life skills. To analyze the data collected in the study, SPSS 21 statistics package software was used. The data were analyzed for normality. As a result of the tests, because it was observed that the data did not have normality distribution, non-parametric tests were utilized. For two-sample comparisons, the Mann Whitney U test was used while the Kruskal Wallis H test was utilized for multiple-sample comparisons. In the study, the level of significance was regarded as p<0.05. The findings of the study indicated that there were significant differences in the life skill levels of the sample group according to the variables of age, gender, grade, the status of exercising and playing in school teams. In conclusion, it was concluded that the life skill levels of 14-year-old students (communication, time management, leadership, teamwork, emotional skills, and social skills) were high while sportive activities were more effective on female students at this age interval compared to male students. It was also observed that participating in school teams enabled positive gains on life skills.